Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: clínica cirúrgica de pequenos animais - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This report describes the activities monitored and/or carried out in the Supervised Curricular Internship in Veterinary Medicine (SCIVM). It was performed in two different locations: Hospital Veterinário Público, Unidade Zona Leste (ANCLIVEPA-SP) and Atendimento Clínico Cirúrgico em Ortopedia Veterinária (ACCOVET). The internship focused, respectively, of soft tissue surgery and orthopedics/neurosurgery, under supervision of Prof. Dr. João Pedro Scussel Feranti. The practical period began on August 1, 2023 and ended on October 31, 2023, summing 474 hours. In both places, It focused on surgical routine, from clinical surgical care to the surgical procedure itself. At the same time, the intern developed teamwork skills, ethics, critical thinking and adaptation to the Veterinary Medicine professional routine . Two cases of interest were chosen for discussion: linear foreign body in a cat and trochlear prosthesis as treatment of patellar luxation in a dog. The SCIVM proved to be extremely important, enabling the student to the professional practice and complementing previous theoretical knowledge.
Report on supervised internship in veterinary medicine. area of concentration: small animal surgical clinic
Keywords: Patellar luxation; Trochlea prothesis; Enterotomia; Pequenos animais; Prótese de tróclea; Corpo estranho linear; Linear foreign body; Enterotomy; Small animal; Luxação de patela; CNPQ::CIENCIAS AGRARIAS